Long Dark Gaps in the Lyβ Forest at z < 6: Evidence of Ultra-late Reionization from XQR-30 Spectra - Yongda Zhu; George D. Becker; Sarah E. I. Bosman; Laura C. Keating; Valentina D’Odorico; Rebecca L. Davies; Holly M. Christenson; Eduardo Bañados; Fuyan Bian; Manuela Bischetti; Huanqing Chen; Frederick B. Davies; et al. (The Astrophysical Journal)
We present a new investigation of the intergalactic medium near reionization using dark gaps in the Ly β forest. With its lower optical depth, Ly β offers a potentially more sensitive probe to any remaining neutral gas compared to the commonly used Ly α line. We identify dark gaps in the Ly β forest using spectra of 42 QSOs at z _em > 5.5, including new data from the XQR-30 VLT Large Programme. Approximately 40% of these QSO spectra exhibit dark gaps longer than 10 h ^−1 Mpc at z ≃ 5.8. By comparing the results to predictions from simulations, we find that the data are broadly consistent both with models where fluctuations in the Ly α forest are caused solely by ionizing ultraviolet background fluctuations and with models that include large neutral hydrogen patches at z < 6 due to a late end to reionization. Of particular interest is a very long ( L = 28 h ^−1 Mpc) and dark ( τ _eff ≳ 6) gap persisting down to z ≃ 5.5 in the Ly β forest of the z = 5.85 QSO PSO J025−11. This gap may support late reionization models with a volume-weighted average neutral hydrogen fraction of 〈 x _H I 〉 ≳ 5% by z = 5.6. Finally, we infer constraints on 〈 x _H I 〉 over 5.5 ≲ z ≲ 6.0 based on the observed Ly β dark gap length distribution and a conservative relationship between gap length and neutral fraction derived from simulations. We find 〈 x _H I 〉 ≤ 0.05, 0.17, and 0.29 at z ≃ 5.55, 5.75, and 5.95, respectively. These constraints are consistent with models where reionization ends significantly later than z = 6.